Racial discrimination as a mediator between criminal justice contact and depressive symptoms among African American women: analysis of the MYPS survey. Issue 4 (19th May 2021) - Kilpatrick, Tanner; Johnson, Elizabeth I.; Bohon, Stephanie A.; Bolland, Anneliese C.; Bolland, John M.
Abstract: This study extends research linking criminal justice contact to mental health by examining the mediating role of perceived racial discrimination among African American women. We hypothesize that criminal justice contact will increase perceptions of racial discrimination, which in turn, will increase the risk of depressive symptoms. Using survey data from 688 African American women living in communities characterized by high poverty, a path analysis was used to test our hypotheses. We find that perceived racial discrimination mediates the relationship between various forms of criminal justice contact and depressive symptoms in women. This evidence underscores the need for additional research on the nature and frequency of discrimination experiences in studies of criminal justice contact and mental health. Results are discussed in terms of implications for criminal justice policies and practice.